The Effect of Different Doses of Vermicompost and Urea Fertilizer on Vegetative Growth of Corn (Zea mays L.) - Ahmad Raksun; Moh. Liwa Ihamdi; I Wayan Merta; I Gde Mertha (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of vermicompost, urea fertilizer and the interaction of vermicompost and urea fertilizer treatments on corn vegetative growth. The research design used was a 2-factor design. The first factor was the application of vermicompost and the second factor was the application of urea fertilizer which was carried out with 3 replications. The doses of vermicompost were 0, 0.5, 1.0, 1.5, and 2.0 kg. The doses of urea fertilizer were 0, 0.6, 1.2, and 1.8 g. The research data were analyzed using Anova. The results of the study were: Vermicompost treatment had a significant effect on stem height, number of leaves and leaf length but had no significant effect on leaf width and corn stem diameter; application of urea fertilizer could increase all measured corn growth parameters; interaction between urea fertilizer and vermicompost treatment had no significant effect on all measured corn growth parameters.